2008
DOI: 10.1136/bjo.2007.124859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self-reported visual impairment on quality of life in the Ibadan study of ageing

Abstract: Impairment of vision is associated with significant decrement in diverse areas of quality of life in this elderly sample. Problems with near vision were nevertheless more likely than those of distant vision to affect quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 17 publications
7
56
1
Order By: Relevance
“…The differences found on the measures of QOL in this study were similar in pattern to those reported in studies from other parts of the world (Bekibele & Gureje, 2008a;Chia et al, 2004;Globe, Wu, Azen, Varma, & The Los Angeles Latino Eye Study Group, 2004;Good, LaGrow, & Alpass, 2008;Horowitz et al, 2005;Jin & Wong, 2008;C. W. Wang et al, 2008;Zimdars, Nazroo, & Gjonça, 2012) making it somewhat more likely that these findings are reflective of the situation in rural Northeast Thailand for older persons who have difficulty with seeing than those reported earlier (La Grow et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The differences found on the measures of QOL in this study were similar in pattern to those reported in studies from other parts of the world (Bekibele & Gureje, 2008a;Chia et al, 2004;Globe, Wu, Azen, Varma, & The Los Angeles Latino Eye Study Group, 2004;Good, LaGrow, & Alpass, 2008;Horowitz et al, 2005;Jin & Wong, 2008;C. W. Wang et al, 2008;Zimdars, Nazroo, & Gjonça, 2012) making it somewhat more likely that these findings are reflective of the situation in rural Northeast Thailand for older persons who have difficulty with seeing than those reported earlier (La Grow et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…As in these studies, those who had difficulty with seeing were found to be older (Horowitz et al, 2005;Jin & Wong, 2008), disproportionately female (Evans et al, 2002;Horowitz et al, 2005;Michon et al, 2002;Nirmalan et al, 2002;Oye & Kuper, 2007;Song et al, 2010;Wong et al, 2008), and to have a poorer perception of health (Chia et al, 2004;LaGrow et al, 2009;J. J. Wang et al, 2000) and lower rating of QOL (Bekibele & Gureje, 2008a;LaGrow, Alpass, Stephens, & Towers, 2011a;LaGrow et al, 2011b;Lamoureux, Fenwick, Moore, Klaic, Borschmann, & Hill, 2009;Nutheti, Shamanna, Nirmalan, Keeffe, Krishnaiah, Rao, & Thomas, 2006;Tran, Mahdi, Sivasubramaniam, Gudlavalleti, Gilbert, Shah, Ezelum, Abubakar, & Bankole, 2011;C. W. Wang, Chan, Ho, & Xiong, 2008) than those who were not.…”
Section: Discussionmentioning
confidence: 90%
“…7 More than half of this study population had no formal education, strengthening the fact that presbyopia correction is required not only for reading and writing but for activities of daily living, such as weeding or winnowing in a Tanzanian population 8 and weaving mats or cleaning grains in a Fijian population. 9 The prevalence of uncorrected presbyopia was reported in 2005 for the first time 10 (although it is not currently included in WHO estimates).…”
Section: Guest Editorialmentioning
confidence: 96%
“…Several studies have shown reduced quality of life in both the developed and developing world. [6][7][8][9] In an elderly …”
Section: How Great Is the Problem?mentioning
confidence: 99%
“…[34][35][36][37][38][39][40] (ii) Health and functional impairments may significantly impact on older persons' quality of life. 41,42 (iii) Within the older population, levels of ill-health and impaired function clearly vary between sociodemographic (e.g., gender, rural/urban, socioeconomic) groups. 28,29,34,[37][38][39][40] Evidence suggests a consistently higher risk of disability, depression, dementia as well as self-reported poor health and function among older women compared to men.…”
Section: Policy Challengesmentioning
confidence: 99%